Big cat dreaming - Wild, Margaret, 1948- (Annick Press ; Distributed in Canada by Firefly Books, 1997)
Do cats dream of fish and meatballs or of when they were kittens, full of fizz and hiss? Grandma dreams about being a girl again and playing hide-and-seek in the dark. But is she only dreaming?